STRATEGI TEKNOLOGI DAN MANAJEMEN INOVASI INDUSTRI TEPUNG KASAVA FERMENTASI - Misgiyarta Misgiyarta; M. Syamsul Maarif; Yandra Arkeman (JURNAL TEKNIK INDUSTRI, 2013)
Many technology research institutes and university research and development can not beapplied by the user community and industry. The result is less a role in improving the welfare ofsociety. Required critical reviews of technology and innovation management strategies togenerate technologies relevant to the needs of society and industry. The study was conducted bytaking the case of the cassava starch fermentation industry. The purpose of this study is (a)acquired technology strategy to improve the quality of fermented cassava flour, added value,competitiveness, and usability, as well as (b) obtained by way of management or management oftechnological innovation that fermented cassava flour can be applied to the industry, providingbenefits , benefits and further foster innovation. Technology strategy fermented cassava flourindustry in the form of: (1) the development of cassava starch fermentation, (2) development ofproduct diversity flour as necessary to market the composite flour technology, (3) flour over thedough expands when made, (4) development of a product of high nutritional value withfortification technology, (5) the development of a more rapid fermentation technology, (6) thedevelopment of fermented cassava flour production technology zero waste. Management ormanagement of innovation is done by: (a) search technology required product market (easy,cheap, fast), (b) selecting appropriate technology industry capacity, (c) development oftechnology that can be controlled, (d) select technology products required penndek term and longterm. Innovation management needs to be done properly so that the resulting innovation candiindustrikan, generate benefits, maximum and sustainable benefits. Management of innovationthat will either encourage the birth of new innovations that can applied in industry and providegreater benefits.